2018
DOI: 10.1371/journal.pone.0195038
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity matching and outcomes after kidney transplantation in the United Kingdom

Abstract: BackgroundKidneys from non-white donors have inferior outcomes, but it is unclear if ethnicity matching between donors and recipients achieves better post kidney transplant outcomes.MethodsWe undertook a retrospective, population cohort study utilising UK Transplant Registry data. The cohort comprised adult, kidney-alone, transplant recipients receiving their first kidney transplant between 2003–2015, with data censored at 1st October 2016. We included 27,970 recipients stratified into white (n = 23,215), blac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…It is known that other posttransplant allograft outcomes vary between ethnic groups. 5 Black patients have been found to require higher doses and longer duration of vasopressors in other shock populations. 6 It is unknown if this is the case in kidney transplant patients.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that other posttransplant allograft outcomes vary between ethnic groups. 5 Black patients have been found to require higher doses and longer duration of vasopressors in other shock populations. 6 It is unknown if this is the case in kidney transplant patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although the predominance of white males within our TxA population is similar to previous studies9 39 the proportion of black, Asian and minority ethnic groups receiving organs in the UK was not reflected in our sample. Although we did not set out to assess ethnicity per se it is plausible that these recipients face additional health and cultural related challenges, for which participation at transplant events holds a lesser priority 40 41. Each TxA’s journey and training experience should thus be considered.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of donor and recipient kidney transplant pairs found that ethnically matched transplants had significantly better graft survival, when compared to non-ethnically matched pairings. However this significance disappeared when adjustment was made for clinical variables including HLA mismatch, sensitization, sex, age and cold ischaemic time 7 . Thus, the impact of shared ancestry between the kidney donor and recipient on graft outcome remains unclear.…”
Section: Introductionmentioning
confidence: 97%